Mario Vegetti, Figure dell’identità greca. L’io, l’anima, il corpo, il soggetto (Materiali di Estetica. Terza serie, 2024)
Filippo Forcignano's review of Mario Vegetti's Figure dell’identità greca. L’io, l’anima, il corpo, il soggetto highlights the work’s meticulous exploration of identity constructs in ancient Greek thought. This collection, featuring twelve seminal essays, underscores Vegetti’s nuanced analysis of key philosophical concepts like justice, the soul, and the body-politic analogy, emphasizing their relevance in both historical and modern contexts. Vegetti rejects simplistic interpretations of Greek psychology, presenting a complex interplay between psyche, soma, and emerging notions of subjectivity. The essays traverse the intersections of medicine, ethics, and politics, demonstrating the critical, interdisciplinary approach that defined Vegetti’s scholarship. Forcignano celebrates the intellectual clarity and moral rigor of Vegetti's work, marking it as an invaluable contribution to the study of ancient philosophy.
Keywords: Ancient Greek; Ancient Philosophy; book review; identity